Sexual Assault on College Campuses: Substance Use, Victim Status Awareness, and Barriers to Reporting - Schwarz, Jill; Gibson, Sandy; Lewis-Ar, Carolynne (Building Healthy Academic Communities Journal, 2017)
Background: Despite the high incidence of estimated sexual assault on college campuses, underreporting is substantial and perpetuated by a culture of rape myths that are pervasive across society in general and college campuses. Aim: The aim of this study was to: examine college student awareness of their own sexual assault victimization status, barriers to reporting, and the prevalence of substance use in sexual assault. Method: This was a cross-sectional mixed-method survey sent to a universal sample of college students from two neighboring institutions of higher education (N=2,724). Results: Results from this survey demonstrated a lack of understanding of what constitutes sexual assault, primarily attributed to the normalization of assault and rape myths. Regardless of victim status awareness, those who were victimized were significantly more likely to use higher levels of alcohol than non-victims, and were less likely to identify their victimization as sexual assault, highlighting the need for college students to understand that alcohol-involved sexual assault is still sexual assault. Conclusions: Overwhelmingly, participants cited the potential consequences as far greater than any potential benefits to reporting sexual assault. Confusion about what constitutes sexual assault and uncertainty of available resources were also recognized as contributing factors in underreporting.